The PENGUIN approach to reconstruct protein interactions at enhancer-promoter regions and its application to prostate cancer - Armaos, Alexandros; Serra, François; Núñez-Carpintero, Iker; Seo, Ji-Heui; Baca, Sylvan C.; Gustincich, Stefano; Valencia, Alfonso; Freedman, Matthew L.; Cirillo, Davide; Giambartolomei, Claudia; Tartaglia, Gian Gaetano (Nature communications, 2023)
We introduce Promoter-Enhancer-Guided Interaction Networks (PENGUIN), a method for studying protein-protein interaction (PPI) networks within enhancer-promoter interactions. PENGUIN integrates H3K27ac-HiChIP data with tissue-specific PPIs to define enhancer-promoter PPI networks (EPINs). We validated PENGUIN using cancer (LNCaP) and benign (LHSAR) prostate cell lines. Our analysis detected EPIN clusters enriched with the architectural protein CTCF, a regulator of enhancer-promoter interactions. CTCF presence was coupled with the prevalence of prostate cancer (PrCa) single nucleotide polymorphisms (SNPs) within the same EPIN clusters, suggesting functional implications in PrCa. Within the EPINs displaying enrichments in both CTCF and PrCa SNPs, we also show enrichment in oncogenes. We substantiated our identified SNPs through CRISPR/Cas9 knockout and RNAi screens experiments. Here we show that PENGUIN provides insights into the intricate interplay between enhancer-promoter interactions and PPI networks, which are crucial for identifying key genes and potential intervention targets. A dedicated server is available at https://penguin.life.bsc.es/ . The authors reconstruct high fidelity networks of protein-protein interactions between promoters and enhancers in prostate cancer and demonstrate the potential of such an analytical framework to obtain actionable insights into the disease and potential therapeutic targets.